Contact type and noncontact type gas flow measuring sensors - Tasnim, Rumana; Arshad, Atika; Saquib, Nazmus; Khan, Sheroz; Ahmed, Musse Mohamud (IIUM Press, 2011)
Gas flow measurement is required in numerous applications; particularly in oil, and gas, nuclear energy, chemical proccssing illdustrics including food, pharmaceutical indUSlryand in agricultural sectors. Gas flow occurs in heat el<changers, steam generators, chemical reactors, oil transportation and other process equipment items. Hence the importance of measuring an accurate flow rate of gascs in pipelincs has been everincreasing in the industrialized regions. Gcnerally any type of gas flow measurement processcs requires gross measurements at some points while more accurate measurements at some other points. As the industry develops it undergoes changes for more comfortable user friendly way of gas flow measurement with improved accuracy. This is coupled with research activities catching demands for exploring alternative non-contact means of electronic measurement, thus putting into fCsearch more of an accurate and reliable measurement rather lIIan just measurement. On tOp of this more customers' awareness is stressing for reliable and robust transducers requiring minimum operation cost with least possibility of industry shutting down just for maintCllllllce reasons, causing loss in revenues